1995
DOI: 10.1159/000119165
|View full text |Cite
|
Sign up to set email alerts
|

The Association of Urinary 5-Hydroxyindoleacetic Acid and Vanillylmandelic Acid in Patients with Generalized Anxiety

Abstract: There is evidence that serotonin and norepinephrine are in some way involved in the pathophysiology of anxiety disorders. Urinary levels of the serotonin metabolite 5-hydroxyindoleacetic acid (5-HIAA) and the norepinephrine metabolite vanillylmandelic acid (VMA) were measured in 46 patients with generalized anxiety disorder. There was a significant association between urinary levels of 5-HIAA and VMA: r = 0.79; p = 0.0001. Possible implications of this finding are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 14 publications
0
11
0
Order By: Relevance
“…10 Symptoms seen in patients with anxiety are triggered by increased sympathetic tone, which leads to increased circulating levels of catecholamines. 18 20 Our study suggests that higher anxiety score is an important risk factor for radial artery vasospasm possibly triggered by increased sympathetic tone in patients with high anxiety scores.…”
Section: Discussionmentioning
confidence: 74%
“…10 Symptoms seen in patients with anxiety are triggered by increased sympathetic tone, which leads to increased circulating levels of catecholamines. 18 20 Our study suggests that higher anxiety score is an important risk factor for radial artery vasospasm possibly triggered by increased sympathetic tone in patients with high anxiety scores.…”
Section: Discussionmentioning
confidence: 74%
“…Markovitz et al [20] found that emotional stress increases platelet activity and suggested that stressors may play an important role in vascular events such as myocardial infarction. In the case of increased stress and anxiety, serotonin binds to 5-HT-2 receptors on platelets and mediates the release of factors that promote platelet aggregation [21]. Pecknold et al [22] found that platelet 5-HT reuptake was increased in patients with major depression accompanying panic disorder.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, serotonin has been shown to increase platelet aggregation and may be a method by which anxiety disorders are associated with increased cardiac events, as anxiety disorders have been associated with abnormalities in the serotonin system [73, 74]. Serotonin binds 5-hydroxytryptamine-2 (5HT-2) receptors on platelets and precipitates the release of factors enhancing platelet aggregation.…”
Section: Mechanisms Mediating the Relationships Between Anxiety Disormentioning
confidence: 99%